THE ROLE OF COFFEE IN INDIA’S AGRICULTURAL EXPORT PORTFOLIO - Dr. S. Prasad (International Educational Journal of Science and Engineering, 2024)
India is the growing exporter of coffee among world competitors. The area, production, and export quantity of coffee registered a similar and fluctuation growth rate during the overall study period. It’s indicating that there is scope for increasing the coffee area and production for strengthening the coffee exports in India. This should be done by adopting new technology and cultivation practices for coffee growing region. The present study has been conducted to examine the area of production of coffee in India. The focus of the study is to analyse the export performance of coffee in India.